The Role of Legal Governance in Marriage to Support the SDGs Goals in the Area of Family Life Based on Law Number 16 of 2019 Concerning Marriage - Riyantika, Annisa; Rodliyah, Nunung; Putri, Ria Wierma; Habiburrahman, Habiburrahman (NEGREI: Academic Journal of Law and Governance, 2024)
This article discusses the role of legal governance in marriage as a means of supporting the achievement of the Sustainable Development Goals (SDGs) in the field of family life. SDGs aim to realize sustainable development, including aspects of quality, healthy, and prosperous family life. It contains targets that are directly related to the protection of human rights, gender equality, and improving family welfare. Legal governance in marriage, such as regulations regarding the rights and obligations of married couples, prevention of domestic violence, and child protection, plays an important role in realizing this. The method used in this study is a normative method with a statutory regulatory approach and literature analysis related to family law and SDGs. The results of the analysis show that effective legal governance in the context of marriage can contribute positively to the achievement of SDGs goals, especially in improving the quality of family life, reducing poverty, and creating gender equality. With good legal governance, the state can provide comprehensive and sustainable legal protection for families, which ultimately supports the achievement of SDGs in the field of family life.